2000
DOI: 10.1021/bi001836h
|View full text |Cite
|
Sign up to set email alerts
|

Role of the β-Strand Insert in the Central Domain of the Fibrinogen γ-Module

Abstract: The crystal structure of the fibrinogen gamma-module (residues gamma143-411) [Yee, V. C., et al. (1997) Structure 5, 125-138] revealed an unusual feature. Namely, residues gamma381-390 in the functionally important COOH-terminal region form a beta-strand that is inserted into an antiparallel beta-sheet of the central domain (gamma192-286), while the rest (gamma393-411) seems to be flexible. To clarify the structural and functional importance of this beta-strand insert, we analyzed the folding status of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Detachment of the C -terminal β strand and its structural consequences observed in simulations confirm the “pull-out hypothesis” (Yakovlev et al, 2000a; Yakovlev et al, 2001), stating that the β strand (residues γ380–392) inserted into the central domain of the γ-nodule, can be removed (“pulled-out”) without destroying its compact structure; yet, such structure without the β strand insert is significantly destabilized. Our results show that the applied force first pulls out the β strand, after which the γ-nodule becomes unstable and falls apart (type 1 transition).…”
Section: Discussionsupporting
confidence: 64%
“…Detachment of the C -terminal β strand and its structural consequences observed in simulations confirm the “pull-out hypothesis” (Yakovlev et al, 2000a; Yakovlev et al, 2001), stating that the β strand (residues γ380–392) inserted into the central domain of the γ-nodule, can be removed (“pulled-out”) without destroying its compact structure; yet, such structure without the β strand insert is significantly destabilized. Our results show that the applied force first pulls out the β strand, after which the γ-nodule becomes unstable and falls apart (type 1 transition).…”
Section: Discussionsupporting
confidence: 64%
“…Based on the position of the g375 residue and the similarity of the b sheet to that of antitrypsin and other serpins, the hypofibrinogenaemia might be a result of domain destabilization, leading to the intermolecular insertion of strand 2. Interestingly, Yakovlev et al [39] have demonstrated that strand 2 of the gD module can be pulled out of the sheet without destroying the compact structure of the domain, lending support to our suggestion that the new Trp residue might allow intermolecular insertion of this strand. An interesting feature of the fibrinogen Aguadilla and Brescia families is the variation in the severity of the liver disease.…”
Section: Mutations Causing Endoplasmic Retentionsupporting
confidence: 76%
“…This suggests that the transverse γ-γ crosslinking is not feasible without substantial elongation of the γ-nodules, which is potentially possible provided that elongation of the γ chain due to the C-terminal β strand pull out occurs. According to this “pull-out” hypothesis, the C-terminal β strand of the γ chain (residues γLys381-Asn390) can be drawn out of the γ-nodule without much perturbation of its native fold (Yakovlev et al, 2000). Consequently, the β strand can extend outwards, increasing the reach of the γ-γ crosslinks.…”
Section: Discussionmentioning
confidence: 99%